Determinación de metabolitos secundarios de hojas de Justicia spicigera, Eryngium foetidum y corteza de Erythrina fusca L. por métodos espectrofotométricos - Chávez Iglesias, Jorge (2021)
The high demand for useful plants for the treatment of different diseases, makes our Loreto region appear as a prodigious alternative of plant species with medicinal benefits, which is why the present work aimed to determine total polyphenol secondary metabolites, saponins and alkaloids in leaves of Justicia spicigera, Eryngium foetidum and bark of Erythrina fusca L. by spectrophotometric methods. Vegetable species selected and collected for convenience. The values obtained from phenolic compounds present in leaves of J. spicigera, E. foetidum and bark of E. fusca L; being much more representative in the plant species E. foetidum who obtained higher results with 41889.987 mg / 100g for total phenols. For flavonoids with 11,406 mg / 100g. Anthocyanins 2.517 mg / 100g and for catechins a value of 0.003 mg / 100g. For alkaloids, J. spicigera leaves presented 6.09 mg / 100g, E. foetidum leaves 41.09 mg / 100g and E. fusca L bark 6.02 mg / 100g respectively. For saponins, leaves of J. spicigera 6.09 mg / 100g, leaves of E. foetidum 41.09 mg / 100g and bark of E. fusca L 6.02 mg / 100g, being important to note that E. foetidum presents a greater quantity, thus concluding that it is the most representative plant species in quantification of secondary metabolites and to which pharmacological activities can be attributed, such as: antioxidant, anti- inflammatory.